Review of Janet Schmalfeldt. 2011. In the Process of Becoming: Analytic and Philosophical Perspectives on Form in Early Nineteenth-Century Music. New York: Oxford University Press - Hansberry, Benjamin Konrad (Current Musicology, 2011)
Classical form has again become a central topic in contemporary music-theoretical discourse largely due to the recent publication of two major treatises on the subject, namely William E. Caplin’s Classical Form (1998) and James Hepokoski and Warren Darcy’s Elements of Sonata Theory (2006). These theoretical titans exemplify, in some ways, two contrasting conceptions of form. While Caplin concerns himself with the ways that sections relate to each other functionally (specifically referring to the importance of harmonies and cadences), Hepokoski and Darcy take a “dialogic” approach, comparing any given sonata (particularly the size, content, and punctuations of sections)with a sort of idealized version of the sonata form. Yet, both theories lack a fully worked out account of time and the emergence of the sonata movement’s sections for a listener, in most cases contenting themselves with identifying sections and examining their relationships to other sections. In In the Process of Becoming: Analytical and Philosophical Perspectives on Form in Early Nineteenth-Century Music, Janet Schmalfeldt develops a theory of form as a process: the form of the work is the development of formal functions in our perception of the piece. Her book expands the processual form theory first laid out in her analysis of Beethoven’s “Tempest” sonata (1995), based on the analysis of Carl Dahlhaus. In his analysis, Dahlhaus argues that to try to classify the opening measures of the “Tempest” sonata (where is the main theme?) is ultimately a fruitless enterprise. Schmalfeldt places her project within what she calls the “Beethoven-Hegelian tradition” taken from Theodor Adorno’s understanding of Beethoven’s music as essentially Hegelian (29-32). Hegel’s metaphysics is known for its use of the dialectic method. Overall, this method is a series of integrations of ideas and their negations that ultimately give rise to the totality of the world or “the Whole;’ being the eventual integration of everything. In this method, an idea is given, which necessarily gives rise to its negation. The given, discrete idea, which starts the dialectic process (e.g., “being” “finite” or “unity”), if it is anything less than “the Whole” possesses conceptual borders; that is, in understanding the concept one must understand its limits. But if there are limits to a concept, then there must be something beyond those limits: there must be something other than the concept under discussion-this is the negation. Despite the negation necessarily being outside the idea, it is nevertheless definitively dependent on the idea, and the idea is dependent in the same way on the negation. That is, we know the idea by understanding its relationship to the negation and vice-versa. Because of the close relationship between the idea and the negation, and both being a part of the Whole, they become integrated into a new idea, a concept that includes both the idea and the negation. With this integrated new idea the dialectic process continues, defining new negations and new integrations until the Whole is completed.